PENINGKATAN LITERASI SISWA MELALUI METODE STORY TELLING DAN MEDIA TEKNOLOGI INTERAKTIF DI SEKOLAH SDN MEKARMULYA III - Lestari, Rival Ludin; Nabilah, Sarah Julia; Azizah, Syifa Nur; Putra, Tri Maulana; Jannah, Wardatul; Khulasoh, Siti (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to improve elementary school students’ literacy skills through the implementation of the storytelling method combined with interactive technology media. The research focused on fifth-grade students at SDN Mekarmulya III, who already possess basic reading skills but still require reinforcement in comprehending reading content, particularly in the context of Islamic Religious Education learning. The research method used was Classroom Action Research (CAR), which consisted of three stages: pre-cycle, cycle I, and cycle II. The results showed a significant improvement in students’ literacy comprehension: from only 11% achieving the minimum mastery criteria in the pre-cycle, to 56% in cycle I after the application of storytelling, and reaching 100% in cycle II following the use of interactive video as a supporting medium. The storytelling method successfully captured students’ attention and increased their participation, while interactive media enhanced their visual and emotional understanding. In conclusion, integrating storytelling with digital technology proved effective in enhancing students' literacy on cognitive, affective, and social levels. This study recommends the broader application of similar strategies in learning, along with support from educational institutions in providing adequate digital facilities.